ZEPLIN-II limits on WIMP-nucelon interactions - Alner, G.; Araujo, H.; Bewick, A.; Bungau, C.; Camanzi, B.; Carson, Michael; Cashmore, R.; Chagani, H.; Chepel, V.; Cline, D.; Davidge, D.; Davies, J.; et al. (2009)
ZEPLIN II is a two-phase xenon detector designed to detect dark matter in the form of Weakly Interacting Massive Particles (WIMPs). Following the first 31-day underground run in Boidby Mine, UK, the collaboration published dark matter Umits in January 2007; the first such limits using two-phase xenon technology. We outline the key detector design, performance and residts here. © 2009 American Institute of Physics.